2021
DOI: 10.3389/fimmu.2020.619408
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan Switches Off the TLR2-Mediated Sperm Recognition and Triggers Sperm Localization in the Bovine Endometrium

Abstract: In mammals, the uterine mucosal immune system simultaneously recognizes and reacts to most bacteria as well as allogenic sperm mainly through the Toll-like receptors (TLR)2/4 signaling pathway. Here, we characterized the impact of pathogen-derived TLR2/4 ligands (peptidoglycan (PGN)/lipopolysaccharide (LPS)) on the immune crosstalk of sperm with the bovine endometrial epithelium. The real-time PCR analysis showed that the presence of low levels of PGN, but not LPS, blocked the sperm-induced inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…When sperm were incubated with luteal phase endometrial explants, it seemed that fewer sperm were gliding over the surface epithelium of luteal endometrium; however, sperm did not enter into the glands they encountered. These observations indicated that the uterine gland is a niche where sperm remain and interact with the uterus (Akthar et al 2020b;Elesh et al 2021). In cattle, this phenomenon was also reported in vivo, where glandular retention of sperm has been observed in histological sections made 24 h after AI (Koyama et al 1986).…”
Section: The Uterine Gland Is a Niche For Sperm In The Uterussupporting
confidence: 55%
See 1 more Smart Citation
“…When sperm were incubated with luteal phase endometrial explants, it seemed that fewer sperm were gliding over the surface epithelium of luteal endometrium; however, sperm did not enter into the glands they encountered. These observations indicated that the uterine gland is a niche where sperm remain and interact with the uterus (Akthar et al 2020b;Elesh et al 2021). In cattle, this phenomenon was also reported in vivo, where glandular retention of sperm has been observed in histological sections made 24 h after AI (Koyama et al 1986).…”
Section: The Uterine Gland Is a Niche For Sperm In The Uterussupporting
confidence: 55%
“…1. We used an array of approaches to elucidate the inflammatory responses of the bovine endometrium to bull sperm, from a simple in vitro co-culture of bovine endometrial epithelial cells (BEECs) with frozen-thawed sperm (Elweza et al 2018;Ezz et al 2019), to an endometrial explant incubation model with fresh (Akthar et al 2020b) and frozen-thawed (Elesh et al 2021) sperm, to the in vivo experiments that were described above (Marey et al 2019). Initially, with our in vitro culture model, only live bull sperm stimulated an inflammatory cascade in BEECs, characterised by increased mRNA expression of the proinflammatory cytokines interleukin 8 (IL8), tumor necrosis factor-alpha (TNFA), interleukin 1 B (IL1B), and nuclear factor-kappa B2 (NFKB2), as well as complement factor 3 (C3) and prostaglandin E synthase (PGES).…”
Section: Sperm Trigger Uterine Innate Immune Responsesmentioning
confidence: 99%
“…Other bacterial species, such as representatives of the Staphylococcus genus, may cause permanent sperm agglutination, through the secretion of agglutination or immobilization factors [ 29 ]. Furthermore, bacterial metabolites such as lipopolysaccharide, hemolysin, and peptidoglycan fragments may cause the flagellum to degenerate, tear off, or break, which has a negative effect on the ability of spermatozoa to reach the oocyte [ 30 , 31 , 32 ]. The exact mechanism by which such damage occurs is not yet fully understood, nevertheless previous reports indicated a significant role of membrane disintegration, promoted by ROS overproduction, either directly by the bacteria or indirectly by damaged spermatozoa [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, preliminary dose-dependent and time-dependent experiments were conducted to identify cytotoxic or detrimental effects of TLR2 antagonist and agonist on sperm motility and viability as analyzed by CASA and flow cytometry ( Supplementary Table S1 and Supplementary Figure S1 ). Next, based on our previous investigations ( Ezz et al, 2019 ; Akthar et al, 2019 ; Morillo, et al, 2020 ; Elesh et al, 2021 ) and our initial trials, the pre-treatment of sperm by TLR2 antagonist (100 µM) or agonist (100 ng ml −1 ) for 30 min was designated as an effective model to test our hypothesis without generating any cytotoxic or detrimental effects on sperm motility and viability.…”
Section: Methodsmentioning
confidence: 99%